2014
DOI: 10.1111/ijcs.12085
|View full text |Cite
|
Sign up to set email alerts
|

Consumer response to food labels in an emerging market: the case of Romania

Abstract: This study investigates consumer response to food labels in an emerging market. More specifically, it measures the levels of awareness, objective and perceived understanding, perceived usefulness and perceived trustworthiness of the most prominent food labels found in the Romanian market. An online survey was conducted with a convenience sample of 428 respondents (45.6% males of an average age of 30.6 years). Results revealed that for most respondents, awareness levels towards food labels are generally low, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This is in line with previous studies from Western European countries, which have shown that the quality label is seen as a major source of information about product quality (Grunert, 2005; Joubert and Poalses, 2012; Garavaglia and Mariani, 2017), whereas in fact knowledge of quality labels is not high. This is also confirmed by studies from Loureiro and McCluskey (2003), Aprile et al (2012), Rousseau and Vranken (2013) and Festila et al (2014), indicating that quality labels are an effective tool for increasing consumer awareness of food quality.…”
Section: Discussionsupporting
confidence: 64%
“…This is in line with previous studies from Western European countries, which have shown that the quality label is seen as a major source of information about product quality (Grunert, 2005; Joubert and Poalses, 2012; Garavaglia and Mariani, 2017), whereas in fact knowledge of quality labels is not high. This is also confirmed by studies from Loureiro and McCluskey (2003), Aprile et al (2012), Rousseau and Vranken (2013) and Festila et al (2014), indicating that quality labels are an effective tool for increasing consumer awareness of food quality.…”
Section: Discussionsupporting
confidence: 64%
“…Other companies have developed or are using carbon labeling or measuring schemes, such as the Finnish Raisio and Fazer Groups, the companies involved in the Product Carbon Footprint (PCF) project in Germany, Unilever using the Cool Farming Tool, and the French Leclerc (Tuomisto et al, 2011). Although the number of large scale success stories is limited, the number of publications which survey groups on label perceptions, preferences, and usefulness is growing and potentially indicates increasing awareness and perhaps the potential for the future use and expansion of labeling (Hu et al, 2012;Sirieix et al, 2013;Zepeda et al, 2013;Chkanikova and Lehner, 2014;Festila et al, 2014;Van Loo et al, 2014). Examples of environmental impact labels include the United Kingdom Tesco grocery store carbon label, the carbon footprint stoplight label designed by Vanclay et al, 2011, and Consumer confusion is a concern for environmental food labeling strategies (Grunert et al, 2014).…”
Section: Environmental Impact Food Labelsmentioning
confidence: 99%
“…Currently, organic products are available in upscale Romanian supermarkets, reflecting the growing interest of the market in organics. Romanian literature in this area mostly concentrates on the labeling scheme and certification process in general [21][22][23] and there is relatively little research on the identification of consumers' perceptions towards organic products [24][25][26][27][28]. The NW Region, which is examined in this study, makes the second-largest contribution to the national GDP (11.3%; 2012 data) and has the third-largest population (13%; 2014 data), the fourth-largest monthly income per person and yearly expenditure level per household (2013 data), and the second-lowest relative at-risk-of-poverty rate (percentage of poor people in the entire population; 2013 data) among the eight Romanian NUTS (Nomenclature of Territorial Units for Statistics) regions.…”
Section: Introductionmentioning
confidence: 99%